PROFESIONALISME PEGAWAI NEGERI SIPIL DALAM PELAYANAN PUBLIK - Mustaqiem Mustaqiem (Badan Kepegawaian Negara | The National Civil Service Agency, 2010)
Civil Servants as public servant must be professional in serving the community in order to obtain ‘feel good service’ for both the provider and receiver. To provide such service, Civil Servant have to work according to prevailed Legislation and upholded by adequate ability and expertise. Therefore Civil Servants have to comprehend the related regulations and obtain sufficient, appropriate education and training. To preserve Civil Servant professionalism in giving public service, employees’ commitments are needed and periodical supervision and evaluation are implemented as well. Keywords: civil servants, professionalism, public service